ANALISIS KINERJA KEUANGAN PEMERINTAH KABUPATEN SUMBAWA TAHUN ANGGARAN 2010-2012 - Rahmawati, Ni Ketut Erna; Putra, I Wayan (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
This study aims to determine the financial performance of Sumbawa district government fiscal year 2010-2012. Variable used are the ratio of the area of ??financial independence, acceptance of PAD effectiveness ratio, the ratio of the efficiency of public expenditures, growth ratio, ratio of proportions and economic ratio. Results of this study showed that the level of financial independence is very low once Sumbawa district, the average level of effectiveness PAD from 2010-2012 which means less effective, the average level of financial efficiency Sumbawa regency of were classified as inefficient, average revenue growth rate showed positive growth. The largest contribution to revenue area is Fund Balance, while the largest contribution to the shopping area is occupied by indirect expenditures, and the average level of local government expenditure Sumbawa classified as economically.
Keywords: Financial performance area , budget and financial ratios